2021
DOI: 10.3390/molecules26226946
|View full text |Cite
|
Sign up to set email alerts
|

The Valorisation of Olive Mill Wastewater from Slovenian Istria by Fe3O4 Particles to Recover Polyphenolic Compounds for the Chemical Specialties Sector

Abstract: Olive oil production using three-phase decanter systems creates olive oil and two by-products: olive mill wastewater (OMWW) and pomace. These by-products contain the highest share of polyphenolic compounds that are known to be associated with beneficial effects on human health. Therefore, they are an attractive source of phenolic compounds for further industrial use in the cosmetic, pharmaceutical and food industries. The use of these phenolics is limited due to difficulties in recovery, high reactivity, compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…The samples were collected at the Franka Marzi olive mill (N 45° 30.6588 E 13° 42.2574, Koper, Slovenian Istria). Details about the samples can be found in our previous research [ 44 ]. Immediately after sampling, OMWW samples were stored in a freezer (−18 °C).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples were collected at the Franka Marzi olive mill (N 45° 30.6588 E 13° 42.2574, Koper, Slovenian Istria). Details about the samples can be found in our previous research [ 44 ]. Immediately after sampling, OMWW samples were stored in a freezer (−18 °C).…”
Section: Methodsmentioning
confidence: 99%
“…HPLC-ESI-Q-TOF-MS analysis, along with compound qualification and quantification, was performed as described in our previous research [ 44 ]. Based on exact mass and fragmentation patterns, twenty phenolic compounds and their isomers were identified by MS: oleoside, hydroxytyrosol glucoside, hydroxtyrosol, elenolic acid glucoside, verbascoside, vanillin, demethyloleuropein, rutin, luteolin- O -glucoside, luteolin rutinoside, nuzhenide, caffeoyl-6-secologanoisde, oleuropein, oleuropein-aglycone di-aldehyde (3,4-DHPEA-EDA), oleuropein aglycone, oleuroside, oleocanthal ( p -HPEA-EDA), and apigenin [ 44 , 45 , 46 ].The calibration plots indicate good correlations between peak areas and commercial standard concentrations. Regression coefficients were higher than 0.990.…”
Section: Methodsmentioning
confidence: 99%
“…Considering the harmful effects of some polyphenols and their derivatives on human health and natural environments, the removal of these compounds from water and wastewater is a great challenge for human and environmental safety, and the search and recognition of effective tools for their treatment, degradation, and removal are worthwhile [2,11]. Accordingly, great efforts have been spent, using physical, chemical, and biological methods to develop and optimize techniques for finding a sustainable solution to this problem.…”
Section: Technologies To Remove Phenolic Compounds From Water Sourcesmentioning
confidence: 99%
“…Phenol (C 6 H 5 OH) or phenic acid is an organic compound that consists of a phenyl group (-C 6 H 5 ) bearing a single hydroxyl group (OH − ) [1]. Polyphenols are an enormous group of secondary plant metabolites characterized by two or more phenolic rings in their chemical structure [2]. Polyphenols could be mainly classified as flavonoids and nonflavonoids, or according to their complexity, as monomeric and polymeric compounds [3].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have shown that the incidence of certain cancers, such as breast and colon cancers, as well as coronary heart disease, is lower in the countries around the Mediterranean basin when compared with the northern European countries [ 1 ]. This may be related to the safer and more protective dietary patterns in the southern countries where olive oil is the primary source of fat [ 2 , 3 ]. Both in vitro and animal studies suggest that the high concentration of phenolic antioxidants in extra virgin olive oil contributes widely to the healthy pattern of the Mediterranean diet [ 4 ].…”
Section: Introductionmentioning
confidence: 99%